A.actinomycetemcomitans adhesi protein increasing IL-8 titre in heart of wistar rat with aggressive periodontitis (Protein adhesin dari A.actinomycetemcomitans meningkatkantiter IL -8 di dalamjantungtikuswistar denganperiodontitis agresif) - Rini Devijanti Ridwan; Retno Indrawati (DiscoverSys Inc., 2014)
Cardiovascular and periodontal diseases are common inflammatory conditions in the human population. Tlymphocytesparticipateinthepathogenesis and inflammatory events of atherosclerosis. These immune cells enter theinflamed artery wall and join macrophages via a number of interferon-c-inducible chemokines. Chemokines (IL-8),cytokines, and growth factors also participate in this process. The interaction between interleukin- 8 and its receptor,CXCR2, can also contribute to lesion formation in mice. The main causes of aggressive periodontitis isActinobacillusactinomycetemcomitans. Previous studies have proven that adhesin protein with 24 kDa molecular weight from A.actinomycetemcomitans is a specific adhesin, this adhesin proteins play a role in the adhesion process on host. thiskind adhesion in the epithelial attachment would lead to colonization and invasion ofA.actinomycetemcomitans thatwill stimulate the host immune response. This study aimed to analyze the influence of induction 24 kDaA.actinomycetemcomitans adhesin protein to the titre of IL-8 in heart of Wistar rat with aggressive periodontitis usingElisa method to measure and analyze the titre of IL-8. After analyzed with analysis of variance, showed significantdifferences of IL-8 titre in the control group and the group with the induction byA.actinomycetemcomitans,A.actinomycetemcomitans plus 24 kDa A.actinomycetemcomitans adhesin protein, and only with 24 kDaA.actinomycetemcomitans adhesin protein. It can be concluded that A.actinomycetemcomitans adhesin protein with 24kDa molecular weight has a role in increasing of IL-8 titre in heart wistar rat with aggressive periodontitis.